The Impact of Import Policy on Farmers' Welfare and Price Stability of Agricultural Commodities in Indonesia - Santanu, Gede (International Journal of Social Science and Business, 2024)
The agricultural sector plays an important role in both economic growth and national food security. The adequacy of domestic production must be able to meet the needs of the community. If not, then the government seeks to import. Fruits are one of the public consumption goods and provide a potential market for local farmers. However, field data shows that Indonesia's fruit imports still tend to be high. This condition further causes the welfare of local farmers to decline. In addition, from a macroeconomic perspective, import policies cause disruptions to price stability in Indonesia. This study aims to explore the impact of import policies on farmers' welfare and price stability in Indonesia. This research is conducted using a qualitative approach based on data from the Central Bureau of Statistics. The results of this study show that the import policy has a negative impact on local fruit farmers and disrupts price stability.